Percepções de impacto da educação empreendedora: implicações para políticas públicas - Jessica Rangel Silva (2020)
Despite highly discussed in Brazil, the entrepreneurship is still incipient in our basic and higher education sectors. Also, the development of entrepreneurial education programs is observed by different theoretical approach and governmental actions. Because of this, the goal with this study is to identify the impact of entrepreneurial education related to former students and use the analysis for possible public policy support. This study has used bibliography, documentary research and data analysis obtained through a questionnaire applied to former students who have joined the “Programa Miniempresa” from 2012 to 2016. From that, it was possible to ensure a theoretical basis to the study, conceptualize and problematize the theme, and map entrepreneurial education programs and methodologies to complement and strengthen the project. The results indicate that entrepreneurial education is based on the development of personal and professional skills, such as taking calculated risks, leadership, commitment, initiative, autonomy, and planning. On the other hand, employability and increased incomes are observed in a lesser extent, refuting the belief in an entrepreneurial education as an employability guarantee. Regarding the public policies, there is constant attempt to implement programs that, however, tend to be interrupted in governmental transitions. That said, the importance of an aligned discourse of entrepreneurial education is emphasized, considering that it is normally accompanied by an illusional view, which only blames the individual for his/her success or failure. Therefore, for the creation of public policies, we highlight the importance of theoretical and methodological validation, management of the knowledge from one government to another and the focus on a formation of humans that respect social, economic, culture and political factors.